Knowledge of Youth Women About Personal Hygiene During Menstruation in RW 007 Gaga Village, Pakuhaji District - Yanasita Mafluha; Siti Nurzannah; Fathia Ihzaniar Ramadhanti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
The purpose of this study was to determine the level of knowledge of young women about personal hygiene during menstruation in young women in RW 007 Desa Gaga Pakuhaji District. This type of research used descriptive research. Descriptive research is a method used to describe or analyze a research result but is not used to make broader conclusions, with a cross-sectional approach, namely data collection for independent variables and dependent variables at one time. The population of this study were 121 young women in RW 007, Desa Gaga, Pakuhaji District. The total sample used was 44 people. The sample in this study were young women in RW 007, Gaga Village, Pakuhaji District. The sampling technique uses the accidental sampling method, which is a sampling technique based on coincidence, that is, anyone who happens to meet the researcher can be used as a sample, if it is deemed that the person who happened to be met is suitable as a data source. The results of this study concluded that The majority of young female respondents in RW 007 Desa Gaga, Pakuhaji District, have good knowledge, namely 24 people (54.5%). The majority of respondents were young women in RW 007 Gaga Village, Pakuhaji District, the frequency of age, education and sources of information, namely 11-14 years old, was 22 people (50%), low education was 25 people (56.8%), information sources were 20 people (45.5%). The majority of female respondents in RW 007 Gaga Village, Pakuhaji District, based on age, the majority of female adolescents who have good knowledge are 90%, namely adolescents aged 18-21 years. The majority of female respondents in RW 007 Desa Gaga, Pakuhaji District, based on education, the majority of female adolescents who have good knowledge, 63.2%, are adolescents with secondary education. The majority of female respondents in RW 007 Desa Gaga, Pakuhaji District, based on sources of information, the majority of young women who have good knowledge 100% are young women who get information from the print media.